Recombinant activated factor VII (Novo7®) in patients with ventricular assist devices: Case report and review of the current literature - Quintel Michael; Bräuer Anselm; Heise Daniel (Journal of Cardiothoracic Surgery, 2007)
Abstract Postoperative bleeding might become a serious problem in the management of cardiac surgical patients, with marked medical and economic impact. In these life-threatening situations, massive haemorrhage represents frequently a combination of surgical and coagulopathic bleeding. Surgical bleeding results from a definite source at the operation site and can be corrected using surgical standard techniques. Acute coagulopathies, in contrast, result from impaired thrombin formation, and require optimized therapeutical strategies. Effective pharmacological treatment will be complicated by the presence of ventricular assist devices (VAD), which necessarily imply effective anticoagulation. In episodes of uncontrolled coagulopathic bleeding, the application of recombinant activated factor VII (rFVIIa) as a effective haemostatic agent has become more and more popular. However, only very few data are available on its use in patients with VAD in place. We researched the PubMed-database for case reports about the use of rFVIIa in patients with VAD and summarized them. In addition, we report a case from our hospital. In all cases cessation of bleeding without any thrombembolic complications could be achieved. In cases of uncontrollable, non-surgical bleeding rFVIIa seems to be a therapeutical option even for patients with VAD.